An Analysis of Hotel Industry Through Value Creation with Special Focus to Business Performance Measurement in Indian Context Measurement - Kumar Siddhartha, Ameya Atul Jani (Mathematical Statistician and Engineering Applications, 2022)
A market with new products, services, or even businesses, the creation of value is crucial. Academics are embracing the fast-growing concept of value creation in an effort to comprehend the methods certain organisations employ to surpass their rivals. The value generation phenomenon is crucial to management literature at both the micro and macro levels. The failure of any business, but notably service organisations, is mostly due to this lack of knowledge. There are many different issues that accompany the subject of value generation. In this article, an analysis of hotel industry through value creation with special focus to business performance measurement in Indian context has been chronicled.